Treatment of Greywater by Using Artocarpus Heterophyllus Seeds as A Natural Coagulant. Issue 1 (1st May 2022) - Cheng, CWJ; Ismail, N; Oh, KS
Abstract: In this study, Artocarpus Heterophyllus seeds is used to treat the greywater. The objectives are to characterize the functional group, zeta potential and the protein content of Artocarpus Heterophyllus seeds and to examine the performance of the seeds in treating greywater by changing the pH, coagulant dose, and mixing effect, as well as comparing them to Aluminium Sulphate (Alum). The functional groups presence in Artocarpus Heterophyllus seeds are hydroxyl group (O-H), amine group (N-H) and carboxylic group (C-O). The zeta potential of Artocarpus Heterophyllus seeds is averaged at -4.14 mV and protein concentration is at 0.294 mg/L. It was found out that Artocarpus Heterophyllus seeds work best at pH 3, 800 mg/L of coagulant dosage and 20 rpm for slow mix and 70 rpm for rapid mixing which resulted in 95.11%, 80.4% and 92.73% removal efficiencies of turbidity, COD and TSS respectively. At pH 6, 200 mg/L of alum coagulant, 40 rpm for slow mix and 150 rpm for quick mix, turbidity, COD, and TSS removal efficiencies were 90.15%, 55.35%, and 96.92%, respectively. Therefore, it shows that Artocarpus Heterophyllus seeds is a better coagulant to treat greywater compared to alum. It has the potential to replace the conventional chemical coagulant.